Composition for binder of lithium-ion battery, method for manufacturing the same, cathode, and lithium-ion battery
Patent Information
- Application Number
- KR1020240061150
- Authority / Receiving Office
- KR · KR
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2024-05-09
- Publication Date
- 2026-09-18
- Estimated Expiration
- 2044-05-09
Smart Images

Figure 112024050403114-PAT00001_ABST
Abstract
Description
Technology Field
[0001] The present invention relates to a binder composition for a lithium-ion battery, a method for manufacturing the same, a slurry composition containing the same, a positive electrode, and a lithium-ion battery. Background Technology
[0002] Electrodes for lithium secondary batteries generally consist of a current collector and an active material layer, wherein the active material layer comprises an active material, a binder, and a conductive material. The binder adheres to the surfaces of the active material particles and the conductive material particles to form the basic framework of the electrode structure, ensures the physical stability of the electrode, and serves to withstand mechanical stress generated during the charging and discharging process.
[0003] Binders are classified into water-based and non-water-based binders; however, due to environmental pollution and high manufacturing costs associated with non-water-based binders, water-based binders are gaining attention. Representative water-based binders include styrene-butadiene rubber (SBR) and carboxymethylcellulose (CMC). While SBR and CMC are environmentally friendly and inexpensive to process because they use water as a solvent, their low adhesion can lead to degradation of battery performance during charging and discharging. Consequently, there is growing interest in binders that improve adhesion and the dispersibility of electrode materials. Prior art literature
[0004] Republic of Korea Published Patent No. 10-2023-0129759 The problem to be solved
[0005] One objective of the present invention is to provide a binder composition for a lithium-ion battery with improved adhesion and dispersibility of the electrode material.
[0006] Another objective of the present invention is to provide a method for manufacturing the binder composition for the lithium-ion battery.
[0007] Another objective of the present invention is to provide a positive electrode slurry composition for a lithium-ion battery that does not use an organic solvent.
[0008] Another objective of the present invention is to provide a positive electrode for a lithium-ion battery comprising an active material layer formed from the positive electrode slurry composition for a lithium-ion battery.
[0009] Another objective of the present invention is to provide a lithium-ion battery in which battery characteristics do not deteriorate as charging and discharging proceed. means of solving the problem
[0010] To achieve the above objective, the present invention provides a binder composition for a lithium-ion battery comprising cellulose nanofibers; and a plurality of different types of aqueous binder compounds.
[0011] In addition, the present invention provides a method for preparing a binder composition for a lithium-ion battery, comprising the steps of: binding lithium ions to functional groups of cellulose nanofibers; and mixing the cellulose nanofibers bound with lithium ions and a plurality of different types of aqueous binder compounds in distilled water.
[0012] In addition, the present invention provides a positive electrode slurry composition for a lithium-ion battery comprising the above-mentioned binder composition for a lithium-ion battery; a positive electrode active material; a conductive material; and distilled water.
[0013] In addition, the present invention provides a positive electrode for a lithium-ion battery comprising: a positive electrode current collector; and an active material layer located on one surface of the positive electrode current collector and formed from a slurry composition for a lithium-ion battery.
[0014] In addition, the present invention provides a lithium-ion battery comprising: the anode; a cathode disposed facing the anode; a separator disposed between the anode and the cathode; and an electrolyte supporting the anode, the cathode, and the separator. Effects of the invention
[0015] According to the present invention, the binder composition of the present invention suppresses the aggregation of the active material and the conductive material due to the excellent water dispersibility of the cellulose nanofiber, thereby allowing the electrode material to be uniformly distributed and the surface of the electrode to which the binder composition is applied can be smooth.
[0016] In addition, the binder composition of the present invention is a cellulose nanofiber COO - Li + The electrode and lithium-ion battery to which the binder composition is applied may include functional groups, and the COO - Li + Due to the functional groups, lithium diffusion performance can be excellent, and battery characteristics may not deteriorate as charging and discharging proceed. Brief explanation of the drawing
[0017] FIG. 1 is a flowchart of a method for manufacturing a binder composition for a lithium-ion battery according to an embodiment of the present invention. Figure 2 is an image of the water dispersion state of CMC and CNF. Figure 3 is a surface observation image of Comparative Example 1. Figure 4 is a scanning electron microscope (SEM) image of Example 1, Example 2, Comparative Example 2, and Comparative Example 3. Figure 5 shows the cycle performance results of Example 3, Example 4, Comparative Example 4, and Comparative Example 5. Figure 6 is the voltage profile at the 100th and 200th cycles of Figure 3. Figure 7 shows the cyclic voltammetry (CV) analysis results of Example 3, Example 4, Comparative Example 4, and Comparative Example 5. FIG. 8 is a COO according to a manufacturing example of the present invention. - Li + This is a schematic diagram of the preparation process for cellulose nanofibers containing functional groups. Figure 9 is the infrared spectral (FT-IR) spectrum of Preparation Example 1. Figure 10 shows the X-ray photoelectron spectroscopy (XPS) results of Preparation Example 1. Figure 11 is a scanning electron microscope (SEM) image of cellulose nanofibers according to a manufacturing example of the present invention. Figure 12 is the X-ray diffraction (XRD) analysis result of cellulose nanofibers according to the manufacturing example of the present invention. Figure 13 shows the cycle performance results of Example 3, Example 6, and Comparative Example 5. Figure 14 is the voltage profile of Example 3, Example 6 and Comparative Example 5. Figure 15 shows the rate capability evaluation results of Example 3, Example 6 and Comparative Example 5. Figure 16 shows the cyclic voltammetry (CV) analysis results of Example 3, Example 6, and Comparative Example 5. Figure 17 shows the peak currents by scanning rate of Example 3, Example 6, and Comparative Example 5. FIG. 18 is a graph of the constant current intermittent titration technique (GITT) of Example 3, Example 6, and Comparative Example 5. Figure 19 shows the electrochemical impedance spectroscopy (EIS) results of Example 3, Example 6, and Comparative Example 5. Specific details for implementing the invention
[0018] Hereinafter, embodiments of the present invention will be described in detail with reference to the attached drawings. Since the present invention is susceptible to various modifications and may take various forms, specific embodiments are illustrated in the drawings and described in detail in the text. However, this is not intended to limit the present invention to the specific disclosed forms, and it should be understood that the invention includes all modifications, equivalents, and substitutions that fall within the spirit and scope of the invention. Similar reference numerals have been used for similar components in the description of each drawing. In the attached drawings, the dimensions of the structures are shown enlarged compared to the actual dimensions for the clarity of the present invention.
[0019] Terms such as "first," "second," etc., may be used to describe various components, but said components should not be limited by said terms. These terms are used solely for the purpose of distinguishing one component from another. For example, without departing from the scope of the present invention, the first component may be named the second component, and similarly, the second component may be named the first component.
[0020] The terms used in this application are used merely to describe specific embodiments and are not intended to limit the invention. The singular expression includes the plural expression unless the context clearly indicates otherwise. In this application, terms such as "comprising" or "having" are intended to specify the existence of the features, numbers, steps, actions, components, parts, or combinations thereof described in the specification, and should be understood as not precluding the existence or addition of one or more other features, numbers, steps, actions, components, parts, or combinations thereof.
[0021] Meanwhile, unless otherwise defined, all terms used herein, including technical or scientific terms, have the same meaning as generally understood by those skilled in the art to which the present invention pertains. Terms such as those defined in commonly used dictionaries should be interpreted as having a meaning consistent with their meaning in the context of the relevant technology, and should not be interpreted in an ideal or overly formal sense unless explicitly defined in this application.
[0023] FIG. 1 is a flowchart of a method for manufacturing a binder composition for a lithium-ion battery according to an embodiment of the present invention.
[0024] Referring to FIG. 1, a method for manufacturing a binder composition for a lithium-ion battery may include the step of binding lithium ions to functional groups of cellulose nanofibers (S110); and the step of mixing the cellulose nanofibers bound with lithium ions and a plurality of different types of aqueous binder compounds in distilled water (S120).
[0025] The step (S110) of binding lithium ions to the functional groups of the cellulose nanofibers above involves dispersing cellulose in a first solvent and reacting it with hydrochloric acid to bind the functional groups of the cellulose nanofibers to COO - Na + A first step of converting from to COOH; a second step of preparing a powder by vacuum filtering the cellulose nanofibers containing the COOH functional group; and dispersing the powder in a second solvent and reacting it with lithium hydroxide to convert the functional group of the cellulose nanofibers from COOH to COO - Li + A third step of converting to; the above COO - Li + The fourth step may include vacuum filtration of cellulose nanofibers containing functional groups to produce a powder.
[0026] In one embodiment, in the first step, the reaction may be carried out at 30 to 60 °C for 1 to 5 hours. For example, the reaction may be carried out at 45 °C for 3 hours. Through the reaction, the functional groups of the cellulose nanofibers are protonated to form COO - Na + It can be converted to COOH.
[0027] In one embodiment, in the second step and the fourth step, the drying may be performed at 50 to 100°C for 5 to 20 hours. For example, it may be performed at 70°C for 12 hours or more.
[0028] In one embodiment, in the third step, the reaction may be carried out at 40 to 80 °C for 5 to 20 hours. For example, it may be carried out at 60 °C for 12 hours or more. Through the reaction, the functional groups of the cellulose nanofibers are lithiated from COOH to COO. - Li + It can be converted into.
[0029] In the step (S120) of mixing the lithium-ion-bonded cellulose nanofibers and different types of water-based binder compounds, the different types of water-based binder compounds may include two or more selected from the group consisting of SBR (Styrene Butadiene Rubber), CMC (carboxymethyl cellulose), PAA (Polyacrylic Acid), and alginate. For example, they may include SBR and CMC.
[0030] In one embodiment, the cellulose nanofiber and the aqueous binder compound can be mixed using a process that typically mixes multiple materials, such as stirring or milling, and there are no particular restrictions on the mixing method.
[0032] A binder composition for a lithium-ion battery according to an embodiment of the present invention can be prepared by the above manufacturing method and may include cellulose nanofibers; and a plurality of different types of aqueous binder compounds.
[0033] In one embodiment, the cellulose nanofiber is COO - Li + It may include functional groups, but is not limited thereto. The cellulose nanofibers above are COO - Li + A small amount of COO in addition to the functional group - Na + and may additionally include COOH functional groups.
[0034] In one embodiment, the content of the cellulose nanofiber may be 5 to 30 weight%, but is not limited thereto. For example, the content of the cellulose nanofiber may be 10 to 20 weight%.
[0035] In one embodiment, the aqueous binder compound may comprise two or more selected from the group consisting of SBR (Styrene Butadiene Rubber), CMC (carboxymethyl cellulose), PAA (Polyacrylic Acid), and alginate, but is not limited thereto. The aqueous binder compound may comprise SBR and CMC mixed in a weight ratio of 1:0.5 to 2.
[0036] In one embodiment, the binder composition for a lithium-ion battery may be composed of the SBR, the CMC, and the cellulose nanofiber in a weight ratio of 4:3 to 5:0.5 to 2. If the CMC exceeds 5 weight percent of the binder composition for a lithium-ion battery, strong aggregation may occur in the electrode material due to the viscosity of the CMC. If the CMC is less than 3 weight percent of the binder composition for a lithium-ion battery, adhesion may decrease, and cracks may occur on the surface. Furthermore, the present invention provides a positive electrode slurry composition for a lithium-ion battery comprising the above-described binder composition for a lithium-ion battery; a positive electrode active material; a conductive material; and distilled water. The positive electrode active material may comprise one or more selected from the group consisting of LFP (LiFePO4), NCM (Li(NiCoMn)O2), LCO (LiCoO2), LMO (LiMn2O4), and NCA (Li(NiCoAl)O2).
[0038] A positive electrode for a lithium-ion battery according to an embodiment of the present invention may include a positive electrode current collector; and an active material layer located on one surface of the positive electrode current collector and formed from a slurry composition for a lithium-ion battery.
[0039] In one embodiment, the positive current collector may be aluminum, but is not limited thereto. A positive current collector typically used in lithium-ion batteries may be applied.
[0041] A lithium-ion battery according to an embodiment of the present invention may include: the positive electrode; a negative electrode disposed facing the positive electrode; a separator disposed between the positive electrode and the negative electrode; and an electrolyte supporting the positive electrode, the negative electrode, and the separator.
[0042] In one embodiment, the negative electrode may be carbon, the separator may be polypropylene, and the electrolyte may be 1.0 M LiPF6 dissolved in EC / DEC (50 / 50, v / v), but is not limited thereto. A negative electrode, separator, and electrolyte typically used in lithium-ion batteries may be applied.
[0044] Hereinafter, the present invention will be described in detail with reference to examples to aid in understanding. However, the following examples are merely illustrative of the content of the present invention and the scope of the present invention is not limited to the following examples. The examples of the present invention are provided to more completely explain the present invention to those with average knowledge in the art.
[0046] <Example 1> Anode
[0047] To utilize cellulose nanofibers (CNF) as a binder for the LFP cathode material of a lithium secondary battery, existing aqueous binder materials, SBR and CMC, were used. A binder was prepared by mixing SBR, CMC, and CNF in a weight ratio of 4:4:2. The binder weight was set to 10 wt% of the slurry used in electrode manufacturing, and a slurry was prepared by mixing LFP (LiFePO4), carbon black (Super P), and distilled water. The cathode was manufactured by coating the above slurry onto aluminum.
[0049] <Example 2> Anode
[0050] The anode was prepared in the same manner as in Example 1, except that the weight ratio of the SBR, CMC, and CNF in Example 1 was set to 4:5:1.
[0052] <Comparative Example 1> Anode
[0053] A cathode was prepared in the same manner as in Example 1, except that the weight ratio of the SBR, CMC, and CNF in Example 1 was set to 5:0:5.
[0055] <Comparative Example 2> Anode
[0056] A cathode was prepared in the same manner as in Example 1, except that the weight ratio of SBR, CMC, and CNF in Example 1 was set to 4:6:0.
[0058] <Comparative Example 3> Anode
[0059] An anode was prepared in the same manner as in Example 1, except that the binder in Example 1 was set to PVDF and NMP (N-methyl-2-pyrrolidone) was used instead of distilled water.
[0061] <Example 3> Half-cell
[0062] A CR2032 specification half-cell was assembled using the anode prepared in Example 1 above. 1.0 M LiPF6 dissolved in EC / DEC (50 / 50, v / v) was used as the electrolyte, polypropylene was used as the separator, and a lithium electrode was used as the negative electrode. The half-cell was assembled in a glove box filled with Ar. The manufactured half-cell was named LFP / C-442.
[0064] <Example 4> Half-cell
[0065] A half-cell was assembled in the same manner as in Example 3, except that the anode prepared in Example 2 was used. The manufactured half-cell was named LFP / C-451.
[0067] <Comparative Example 4> Half-cell
[0068] A half-cell was assembled in the same manner as in Example 3, except that the anode prepared in Comparative Example 2 was used. The manufactured half-cell was named LFP / C-460.
[0070] <Comparative Example 5> Half-cell
[0071] A half-cell was assembled in the same manner as in Example 3, except that the anode prepared in Comparative Example 3 was used. The prepared half-cell was named LFP / C-PVDF.
[0073] <Experimental Example 1>
[0074] Figure 2 shows images of CMC and CNF in a water dispersion state. Figure 2 shows 25 mg each of CMC and CNF dispersed in 1 ml of distilled water and applied to a slide glass. It was confirmed that CMC has higher viscosity than CNF.
[0075] Figure 3 is a surface observation image of Comparative Example 1. It was confirmed that the SBR and CNF mixture had low viscosity, so smooth electrode coating was not achieved. When combined with the results of Figure 2, it was determined that an appropriate amount of CMC is required for the SBR and CNF mixture.
[0076] Figure 4 shows scanning electron microscope (SEM) images of Example 1, Example 2, Comparative Example 2, and Comparative Example 3. Comparative Example 3 is a case where PVDF was used as a binder, and cracks occurred on the electrode surface due to low adhesion properties. When examining Comparative Example 2, Example 1, and Example 2, as the ratio of cellulose nanofibers (CNF) increased from 0 to 2, the electrode surface became smoother and the electrode material showed a more uniform distribution. This is because the aggregation of the active material and the conductive material was reduced due to the excellent water dispersibility, which is an inherent characteristic of CNF.
[0077] Figure 5 shows the cycle performance results of Example 3, Example 4, Comparative Example 4, and Comparative Example 5, and Figure 6 shows the voltage profiles at the 100th and 200th cycles of Figure 3. In Figure 5, it was confirmed that the performance of the battery improved as the CNF content increased, and in particular, in the case of LFP / C-442, it was confirmed that it maintained a higher capacity than when using a PVDF binder. In Figure 6, the difference between charge and discharge voltages was compared at a specific capacity of 50 mAh / g. A lower voltage at this point indicates a lower polarization resistance of the electrode. LFP / C-442 recorded the lowest electrode value. This is because, as shown in the SEM image results of Figure 4, the dispersion and distribution of the electrode material were improved, thereby improving the conductive pathway and electron transfer resistance.
[0078] Figure 7 shows the results of the cyclic voltammetry (CV) analysis of Example 3, Example 4, and Comparative Example 4. When 5 cycles were measured at a scan rate of 0.3 mV / s, the peaks of the graphs for LFP / C-460 and LFP / C-451 became narrow and sharp; however, for both ratios, the peaks of the graphs did not stabilize with each cycle and were measured at different positions and shapes. This indicates that the reversibility of the electrochemical reaction is unstable. On the other hand, it was confirmed that LFP / C-442 was measured with similar voltage and current during 5 cycles, resulting in a graph with a stabilized shape.
[0080] <Preparation Example 1> COO - Li + Cellulose nanofibers containing functional groups
[0081] FIG. 8 is a COO according to a manufacturing example of the present invention. - Li + This is a schematic diagram of the preparation process of cellulose nanofibers containing functional groups. Referring to Fig. 8, the COO of conventional cellulose nanofibers - Na + After converting the functional group to COOH, the COOH is lithiated to COO - Li + It was converted into a functional group.
[0082] 500 mg of powdered cellulose nanofibers was dispersed in 100 ml of a mixed solution (ethanol:distilled water = 85:15 v / v) for at least 30 minutes, then 20 ml of 20 wt% HCl was added and stirred at 45 °C for 3 hours. After stirring, the powder was vacuum filtered and washed with the mixed solution. The washed powder was dried at 70 °C for 12 hours. COO - Li + To substitute, the dried powder was dispersed in 25 ml of anhydrous ethanol, then 5 ml of 7 wt% LiOH was added and stirred at 60°C for at least 12 hours. - Li +The powder substituted with was vacuum filtered and washed with anhydrous ethanol. After washing, it was dried at 70 °C for 12 hours to obtain COO - Li + Cellulose nanofibers containing functional groups were obtained.
[0083] The C6-carboxylate group of the cellulose nanofiber of Preparation Example 1 is COO - Na + , COOH, COO - Li + Since it is converted into, the cellulose nanofibers according to each functional group were named CNF-Na, CNF-H, and CNF-Li.
[0085] <Example 5> Anode
[0086] A cathode was prepared in the same manner as in Example 1, except that CNF-Li prepared in Preparation Example 1 was used instead of CNF in Example 1.
[0088] <Example 6> Half-cell
[0089] A half-cell was assembled in the same manner as in Example 3, except that the anode prepared in Example 5 was used. The manufactured half-cell was named LFP / C - 442@Li.
[0091] <Experimental Example 2>
[0092] Figure 9 is the infrared spectral (FT-IR) spectrum of Preparation Example 1, and Figure 10 is the X-ray photoelectron spectroscopy (XPS) result of Preparation Example 1. According to the FT-IR analysis results, the peak shifts of CNF-Na, CNF-H, and CNF-Li were confirmed in the specified order, and the presence of Na and Li was confirmed through XPS.
[0093] Figure 11 is a scanning electron microscope (SEM) image of cellulose nanofibers according to an example of the present invention, and Figure 12 is an X-ray diffraction (XRD) analysis result of cellulose nanofibers according to an example of the present invention. In Figure 11, it was confirmed that CNF-Na, CNF-H, and CNF-Li induced chemical changes in functional groups without separate morphological changes. In Figure 12, it was confirmed that CNF-Na, CNF-H, and CNF-Li did not show significant changes in amorphousness and crystallinity despite changes in functional groups.
[0094] Figure 13 shows the cycle performance results of Example 3, Example 6, and Comparative Example 5. It was confirmed that LFP / C-442@Li has superior performance at high speeds of 5C compared to LFP / C-442 and LFP / C-PVDF.
[0095] Figure 14 shows the voltage profiles of Example 3, Example 6, and Comparative Example 5. In Figure 13, the charge-discharge voltage difference was compared starting from a specific capacity of 50 mAh / g. It was confirmed that LFP / C-442@Li has a small charge-discharge voltage difference, indicating improved performance through low polarization resistance.
[0096] Figure 15 shows the rate capability evaluation results of Example 3, Example 6, and Comparative Example 5. The rate capability evaluation was performed at current densities of 0.1, 0.2, 0.5, 1, 2, 5, 10, and 0.1 C. In the rate capability evaluation as well, it was confirmed that LFP / C-442@Li has excellent performance at high speeds.
[0097] Figure 16 shows the cyclic voltammetry (CV) analysis results of Example 3, Example 6, and Comparative Example 5. Measurements were taken at scan rates of 0.1, 0.2, 0.3, 0.5, 0.7, and 1.0 mV / s. In the graph, the narrower and sharper the width of the two peaks, the better the electrochemical response. It was confirmed that the peak of LFP / C-442@Li was the narrowest and sharpest.
[0098] Figure 17 shows the peak currents according to the scan rate of Example 3, Example 6, and Comparative Example 5. In Figure 17, a steeper slope indicates better lithium diffusion within the electrode, and it was confirmed that LFP / C-442@Li exhibited the best diffusion.
[0099] Figure 18 is a graph of the constant current intermittent titration technique (GITT) for Example 3, Example 6, and Comparative Example 5. The analysis was performed with a 2-hour rest period following the application of a current of 0.1C for 30 minutes. As a result of calculating the diffusion coefficient from the experimental results by GITT, LFP / C - 442@Li showed the highest value, which indicates excellent lithium diffusion.
[0100] Figure 19 shows the electrochemical impedance spectroscopy (EIS) results of Example 3, Example 6, and Comparative Example 5. The EIS analysis results confirmed that Example 3, Example 6, and Comparative Example 5 all had similar charge transfer resistances prior to the cycle, but LFP / C-442@Li had the smallest charge transfer resistance after 150 cycles at a rate of 5C. This trend was the same as that shown in Figures 16 to 18.
[0102] Although the present invention has been described above with reference to preferred embodiments, those skilled in the art will understand that various modifications and changes can be made to the invention without departing from the spirit and scope of the invention as set forth in the following claims.
Claims
Claim 1 delete Claim 2 delete Claim 3 delete Claim 4 delete Claim 5 delete Claim 6 delete Claim 7 A method for preparing a binder composition for a lithium-ion battery, comprising: a step of binding lithium ions to functional groups of cellulose nanofibers; and a step of mixing the cellulose nanofibers bound with lithium ions and a plurality of different types of aqueous binder compounds; wherein the step of binding lithium ions to functional groups of cellulose nanofibers comprises dispersing cellulose in a first solvent and reacting it with hydrochloric acid to bind the functional groups of the cellulose nanofibers to COO - Na + A first step of converting from to COOH; a second step of preparing a powder by vacuum filtering the cellulose nanofibers containing the COOH functional group; and dispersing the powder in a second solvent and reacting it with lithium hydroxide to convert the functional group of the cellulose nanofibers from COOH to COO - Li + A third step of converting to; and the above COO - Li + A method for preparing a binder composition for a lithium-ion battery, comprising: a fourth step of preparing a powder from cellulose nanofibers containing functional groups by vacuum filtration. Claim 8 delete Claim 9 A method for preparing a binder composition for a lithium-ion battery according to claim 7, wherein in the first step, the reaction is performed at 30 to 60 ℃ for 1 to 5 hours. Claim 10 A method for preparing a binder composition for a lithium-ion battery according to claim 7, wherein in the third step, the reaction is performed at 40 to 80 ℃ for 5 to 20 hours. Claim 11 A method for manufacturing a binder composition for a lithium-ion battery according to claim 7, wherein the second step and the fourth step are performed at 50 to 100 ℃ for 5 to 20 hours. Claim 12 delete Claim 13 delete Claim 14 delete Claim 15 delete
Citation Information
Patent Citations
Binding agent, electrode slurry, electrode and method of manufacturing the same, and secondary battery
JP2017130451A
Slurry composition for use in forming lithium-ion secondary battery electrode, containing cellulose fiber as binder, and lithium-ion secondary battery electrode
KR1020140082975A
